2023
DOI: 10.1021/acs.energyfuels.3c03403
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic CO2 Injection in Tight Rocks: Implications for Enhanced Oil Recovery and Carbon Geo-Storage

Hamad AlKharraa,
Karl-Heinz Wolf,
Abdulrahman AlQuraishi
et al.

Abstract: Carbon dioxide (CO2) injection has been widely used in conventional reservoirs for enhanced oil recovery and CO2 sequestration. Nevertheless, the effectiveness of CO2 injection in tight reservoirs is limited due to diagenetic processes that impact displacement efficiency. This research work assesses the performance of CO2 injection in tight reservoirs and evaluates oil mobilization and fluid distribution within the rock pore systems. A set of experiments, including routine core analysis, X-ray diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Even Wang et al 37 investigated the CO 2 injection in tight gas and found the same; i.e., high pressure helps gas flow more easily, and more water hinders gas flow. AlKharraa et al 38 investigated the effect of CO 2 injection in tight rocks. Tight rocks hold a lot of oil, but getting it out is tricky as a result of the ultralow permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Even Wang et al 37 investigated the CO 2 injection in tight gas and found the same; i.e., high pressure helps gas flow more easily, and more water hinders gas flow. AlKharraa et al 38 investigated the effect of CO 2 injection in tight rocks. Tight rocks hold a lot of oil, but getting it out is tricky as a result of the ultralow permeability.…”
Section: Introductionmentioning
confidence: 99%